2020
DOI: 10.1111/codi.14993
|View full text |Cite
|
Sign up to set email alerts
|

Using preoperative three‐dimensional endoanal ultrasound to determine operative procedure in patients with perianal fistulas

Abstract: AimAccurate preoperative identification of perianal fistula tracts and internal openings can facilitate the choice of surgical procedure and may lead to improved healing rates. Our aim was to explore the effectiveness of three‐dimensional endoanal ultrasound (3D‐EAUS) in determining the type of perianal fistula and planning operative management.MethodThis was a cohort longitudinal study. Patients with perianal fistulas from January 2017 to January 2018 who underwent 3D‐EAUS and subsequent surgery were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The diagnostic accuracy when any 2 of the 3 mentioned tests were combined was 100% [23]. Other published articles also suggested that if pelvic MRI and EAUS were combined preoperatively, this could improve their total diagnostic accuracy [34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy when any 2 of the 3 mentioned tests were combined was 100% [23]. Other published articles also suggested that if pelvic MRI and EAUS were combined preoperatively, this could improve their total diagnostic accuracy [34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The value of preoperative fistula imaging is the detection of tracts and internal openings, which might be missed during surgical exploration [ 11 ]. Accurate preoperative imaging and classification of the type of perianal fistula can guide the choice of the appropriate surgical procedure, thereby possibly improving healing rates [ 12 ]. MRI and 3D endoanal ultrasound (EAUS) for the diagnosis of anal fistula have been proven to be accurate and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical classifications of anal fistulas as intersphincteric, transsphincteric, suprasphincteric, and extrasphincteric are useful 8 . Therefore, careful radiological assessment of the fistula for obtaining more details such as type of fistulas, location of the internal opening of fistulas, and fistula's branches seems to be necessary for having a better surgical plan and decreasing the risk of recurrences after surgery 9–12 . At present time MRI and endoanal ultrasonography are two acceptable modalities for assessing anal fistulas 13–17 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, careful radiological assessment of the fistula for obtaining more details such as type of fistulas, location of the internal opening of fistulas, and fistula's branches seems to be necessary for having a better surgical plan and decreasing the risk of recurrences after surgery. [9][10][11][12] At present time MRI and endoanal ultrasonography are two acceptable modalities for assessing anal fistulas. [13][14][15][16][17] Each of these imaging tools has more than 85% accuracy, and in combination, the sensitivity is near 100%.…”
mentioning
confidence: 99%